2023
DOI: 10.3390/genes14020323
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution Characteristics of Viruses from Soda Lakes

Abstract: Viruses are the most abundant living things and a source of genetic variation. Despite recent research, we know little about their biodiversity and geographic distribution. We used different bioinformatics tools, MG-RAST, genome detective web tools, and GenomeVx, to describe the first metagenomic examination of haloviruses in Wadi Al-Natrun. The discovered viromes had remarkably different taxonomic compositions. Most sequences were derived from double-stranded DNA viruses, especially from Myoviridae, Podovirid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…According to recent statistics, viruses are thought to be responsible for 2,000,000 human fatalities annually throughout the world [ 25 ]. SARS-CoV), MERS-CoV, and SARS-CoV-2 have all occurred in the world [ 26 , 27 ]. The highly pathogenic MERS-CoV was initially discovered in the KSA in 2012 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent statistics, viruses are thought to be responsible for 2,000,000 human fatalities annually throughout the world [ 25 ]. SARS-CoV), MERS-CoV, and SARS-CoV-2 have all occurred in the world [ 26 , 27 ]. The highly pathogenic MERS-CoV was initially discovered in the KSA in 2012 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most acylglycerides (99%) constitute argan oil, whether edible or cosmetic grade (primarily triglycerides). The remaining one percent, known as unsaponifiable matter, comprises xanthophylls, triterpene alcohols, carotenes, and tocopherols ( Charrouf and Guillaume, 1999 ; ZeinEldin et al, 2023 ). The primary fatty acids that constitute acylglycerides are oleic and linoleic acids, which account for 43%–49% and 29%–36%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even though argan seed cake has primarily been used for animal feed ( Cherki et al, 2006 ), it has also been suggested as a natural moisturizer and exfoliator for use in commercial shampoos and lotions to heal wounds, sprains, and scabies topically. Recent studies show that the ethanol extract of argan seed cake may be utilized as a natural lightening and pharmacological therapy for treating hyperpigmentation issues because of its effects on melanogenesis ( Bourhim et al, 2018 ; Bourhim et al, 2021 ; ZeinEldin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most acylglycerides (99%) make up argan oil, whether edible or cosmetic grade (primarily triglycerides). The remaining one percent, known as unsaponi able matter, comprises xanthophylls, triterpene alcohols, carotenes, and tocopherols 10,34 . The primary fatty acids that makeup acylglycerides are oleic and linoleic acid, which account for 43-49% and 29-36%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the ethanol extract of argan seed cake may be utilized as a natural lightening and pharmacological therapy for treating hyperpigmentation issues because of its effects on melanogenesis. [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%